Safety and therapeutic effects of personalized transcranial direct current stimulation based on electrical field simulation for prolonged disorders of consciousness: study protocol for a multi-center, double-blind, randomized controlled trial - Yoon, Mi-Jeong; Oh, Hyun Mi; Kim, TaeYeong; Choi, Soo-Jin; Choi, Woo Hee; Jung, Hong Soo; Lim, Sung Chul; Yoo, Yeun Jie; Park, Hye Jung; Hong, Bo Young; Park, Geun-Young; Kim, Donghyeon; et al. (Frontiers in Neurology, 2023)
Background Disorders of consciousness (DOC) resulting from acquired brain injury (ABI) increase the mortality rate of patients, complicate rehabilitation, and increase the physical and economic burden that DOC imposes on patients and their families. Thus, treatment to promote early awakening from DOC is vital. Transcranial direct current stimulation (tDCS) has shown great potential for promoting neuro-electrochemical activity. However, previous tDCS studies did not consider structural damage or head and brain lesions, so the applicability of the results to all DOC patients was limited. In this study, to establish a patient-specific tDCS treatment plan considering the brain lesions of and damage sustained by DOC patients, we considered the electric field calculated by a the “finite electric” three-dimensional brain model based on magnetic resonance images. This protocol was developed to aid tDCS treatment of actual patients, and to verify its safety and effectiveness. Methods/design Twenty-four patients with DOC after ABI will be enrolled in this cross-over trial. All participants will receive typical rehabilitation combined with sham tDCS and typical rehabilitation plus personalized tDCS (P-tDCS). Each interventional period will last 2 weeks (30 min/day, 5 days/week). The primary outcome [score on the Korean version of the Coma Recovery Scale-Revised (K-CRS-R)] will be assessed at baseline and the end of the first day of the intervention. Secondary outcomes (K-CRS-R at 1 week and 2 weeks after experimental session and quantitative EEG changes quantitative electroencephalography changes) will be measured at baseline and the end of week 4. Adverse events will be recorded during each treatment session. Discussion For patients with neurological disorders, tDCS has served as a painless, non-invasive, easily applied, and effective therapy for several decades, and there is some evidence that it can improve the level of consciousness of patients with DOC. However, variability in the effects on consciousness among subjects have been reported and personalized strategies are lacking. This protocol is for a randomized controlled trial designed to validate the effectiveness and safety of P-tDCS combined with typical rehabilitation for DOC. Clinical trial registration https://cris.nih.go.kr, identifier KCT0007157.